2016
DOI: 10.1016/j.jnucmat.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

The role of dislocation channeling in IASCC initiation of neutron irradiated stainless steel

Abstract: This study intended to understand how dislocation channeling affects IASCC initiation using a novel four-point bend test. Stainless steels used in this study (irradiated in the BOR-60 reactor) included a commercial purity 304L alloy irradiated to 5.5, 10.2, and 47.5 dpa, and two high purity alloys, Fe-18Cr-12Ni and Fe-18Cr-25Ni, irradiated to ~10 dpa. IASCC was enhanced by MnS inclusions, which dissolve in the NWC environment and form oxide caps, creating a crevice condition with a high propensity for crack in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…However, just as a perfect a 2 011 glide dislocation progresses on a (111) plane by the passage of two Shockley partials ( a 6 112 + a 6 121 ), there is no reason why there cannot be two or more twinning operations in the same volume of material producing large shear strains. In many cases where strain localization is linked to cracking, the authors refer to stress amplification, but that does not necessarily have to be at the level needed to create a Stroh-type crack; rather, it is at a level where the interaction with surface inclusions or surface oxide initiates cracking when coupled with some SCC mechanism [57,58].…”
Section: Crackingmentioning
confidence: 99%
“…However, just as a perfect a 2 011 glide dislocation progresses on a (111) plane by the passage of two Shockley partials ( a 6 112 + a 6 121 ), there is no reason why there cannot be two or more twinning operations in the same volume of material producing large shear strains. In many cases where strain localization is linked to cracking, the authors refer to stress amplification, but that does not necessarily have to be at the level needed to create a Stroh-type crack; rather, it is at a level where the interaction with surface inclusions or surface oxide initiates cracking when coupled with some SCC mechanism [57,58].…”
Section: Crackingmentioning
confidence: 99%
“…Dislocation channel formation and the appearance of dislocation pileups [2] may directly preclude stress corrosion crack initiation [4][5][6]. It has also been demonstrated that dislocation channel formation may occur at external stresses below yield stress [7,8], so it is important to understand dislocation evolution under these conditions.…”
Section: Background and Motivationmentioning
confidence: 99%
“…The slip discontinuity was more prevalent on GHAB along grains which underwent strain owing to suitable orientation to load axis. In [58,59], there were given detailed insights of IASCC initiation of A304L irradiated in BOR-60 at 320 • C to 5.5 dpa. It was referred that, to initiate IG cracks, the applied stress was lower than the yield strength, but dislocation channels and MnS inclusions were observed around GB, where the IASCC cracks initiated.…”
Section: Irradiation Assisted Scc Fracturementioning
confidence: 99%